A Meta-Analysis on Democracies in Indonesia - Syamsul Bahri Abd. Rasyid; Achmad Nurmandi; Salahudin; Dian Eka Rahmawati (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2024)
This research intends to describe the map of the progress of democracy studies in Indonesia. The study was performed by searching the Scopus database using the keyword “Democracy in Indonesia.” The search results are then descriptively analyzed based on the year of publishing, the number of publications, the most regularly published writer, source of the article, country of publication, and association. Data is exported in the RIS format to receive a research-creation diagram. The exported data is then interpreted and evaluated using the VOSviewer program to classify the bibliometric map and the Nvivo 12 plus software to determine the most general categorization of themes and topics. Via network visualization, lines between nodes represent the relationships (edges) between inter-nodes. The other lines of connection between nodes, the closer the relationships with records are. Meanwhile, with the visualization of density, it was seen that if the color visualized was getting redder, the subject had been researched a lot, although the topic was only barely researched if it was getting greener. Indonesia's R&D maps on democracy are grouped into six key themes: democracy, politics, social, political, local, and electoral, while political, democracy, politics, social, and growth are the most dominant themes.